Konsep Etnomatematika Batik Tradisional Jawa Sebagai Pengembangan Media Pembelajaran Matematika - Ari Irawan; Mei Lestari; Wanti Rahayu (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
The purpose of this study is to reveal the types of batik patterns that can be used as a medium for learning mathematics, especially in the transformation geometry material. In addition, making applications for learning mathematics using ethnomathematical elements in traditional batik patterns in West Java, Central Java and East Java. This research method is RnD (Research and Development) with ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). The stages that will be discussed in this research are identification, classification, and analysis of batik patterns in Java. The results of this study are the identification of batik patterns on the island of Java, classifying types and existing batik motifs and analyzing batik motifs using elements of an ethnomathematical approach. The result suggests batik patterns can be used as a medium for learning mathematics by using an ethnomathematical element approach as learning both mathematics education and student character education.